2002
DOI: 10.1021/jo015864x
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Bafilomycin V1:  A Methanolysis Product of the Macrolide Bafilomycin C2

Abstract: A synthesis of bafilomycin V(1), a methanolysis product of the macrolide natural product bafilomycin C(2), is described. The route utilizes chiral nonracemic allenylzinc reagents, prepared in situ from propargylic mesylates, to access key segments of this methyl ester. The acetylenic moieties of the derived homopropargylic alcohol adducts play an important role in further elaboration of these subunits. Final assemblage of the 25-carbon chain, containing 12 stereocenters, an alpha-methoxy Z,E 1,3-dienic ester, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 55 publications
1
40
0
1
Order By: Relevance
“…Gratifyingly, this new approach culminated in the development of the general and efficient synthesis of the unprecedented subfamily of 1,3-di-tert-alkyl-4,5-dimethylimidazolium salts 1 a-d starting from rac-but-3-yn-2-yl methanesulfonate [19] (Scheme 1 and Table 1). …”
mentioning
confidence: 99%
“…Gratifyingly, this new approach culminated in the development of the general and efficient synthesis of the unprecedented subfamily of 1,3-di-tert-alkyl-4,5-dimethylimidazolium salts 1 a-d starting from rac-but-3-yn-2-yl methanesulfonate [19] (Scheme 1 and Table 1). …”
mentioning
confidence: 99%
“…Final assembly of the 25-carbon chain (containing 12 stereocenters) of bafilomycin V1 by Marshall and Adams [110] involved an acetylenederived vinyltin and a vinyl iodide of similar complexity. Paquette et al [111] reported a highly convergent three-component 64-step total synthesis of the potent immunosuppressive agent (−)-sanglifehrin A, the penultimate step involving a vinyl-vinyl coupling.…”
Section: Vinyl-vinyl Couplingsmentioning
confidence: 99%
“…In 2002, Marshall and Adams [90] reported a total synthesis of bafilomycin V 1 (112) [8], a seco-ester product obtained from methanolysis of bafilomycin C 2 (111) (Fig. 5), demonstrating stereoselective additions of non-racemic chiral allenylzinc reagents [91] with aldehydes for installation of various stereotriads.…”
Section: E Marshall's Total Synthesis Of Bafilomycin Vmentioning
confidence: 99%
“…Attempts were also made to effect macrolactonization of the seco-acid obtained from the methyl ester 135 (KOTMS, THF, rt) [103] in quantitative yield. However, macrolactonization failed with both the Yamaguchi method [51] and the "double activation" method based on 2,2'-dipyridyl disulfide and Ph 3 P [104], presumably due to decomposition of the activated intermediate [90]. At this point, it is interesting to examine the structural difference in the seco-acid 45 (Scheme 6) [41], the seco-acid 75b (Scheme 11) [55], and the seco-acid of 135 [90].…”
mentioning
confidence: 99%
See 1 more Smart Citation